The Application of Visual-Pictures Sequence to Increase Students' Writing Ability - Nashruddin Nashruddin; Fiptar Abdi Alam; Zulfikat Alam; Niskarlina Niskarlina (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The present study aims to determine how the use of visual-pictures sequence as learning media can increase students’ ability in writing which include topic sentences, supporting sentences, and closing sentences. Researchers apply classroom action research, which has been implemented in two cycles. Each cycle consists of four learning meetings. This study used a written test and an observation sheet as data collection instruments, involving 20 students of class XI-IPA at SMA Muhammadiyah 7 Makassar as participants. The results show that visual pictures sequence in learning can increase students’ ability in writing based on the evaluation result to participants. In addition, based on the observation result, the application of pictures sequence in learning can increase students’ activity and self-confidence, resulting in a change in attitude for the better in the learning process.